Business Environment and Dual-Track Private Sector Development : China's Experience in Two Crucial Decades - Long, Cheryl Xiaoning; Xu, L. Colin; Yang, Jin (World Bank, Washington, DC, 2020)
A void in the literature on the business environment is how it evolves over time. Focusing on China during its crucial two decades of transition (from the early 1990s to the early 2010s), this paper documents how the country's business environment and the characteristics of entrepreneurs evolved, along with the role played by local governments. Relying on multiple comprehensive data sets, the paper shows that many aspects of local business environments improved: infrastructure, development of the court system, and access to external finance. Meanwhile, the share of politically connected private firms remained large, and their advantage in accessing key resources increased. Under this dual-track private sector development, private firms became larger and more innovative and adopted more formal corporate governance mechanisms. Entrepreneurs became much better educated, with more diverse sectoral experience. Market competition increased over time, especially after China's World Trade Organization entry. The paper offers suggestive evidence that this dual track development had negative consequences, such as a lower tendency to innovate by politically connected firms.